Treatment of Nontuberculous Mycobacterial (NTM) Pulmonary Infection in the US Bronchiectasis and NTM Registry: Treatment Patterns, Adverse Events, and Adherence to American Thoracic Society/Infectious Disease Society of America Treatment Guidelines. (22nd September 2022) - Ku, Jennifer H; Henkle, Emily; Aksamit, Timothy R; Barker, Alan; Brunton, Amanda E; Winthrop, Kevin L
Abstract: Among 1038 participants with pulmonary Mycobacterium avium complex and 120 with Mycobacterium abscessus enrolled in the US Bronchiectasis and NTM Research Registry, less than half received antibiotic therapy in the 24 months before registry enrollment, of which less than half were guideline based. Adverse effects occurred in 21% of therapy recipients, of whom 33% discontinued therapy.